Kadar Hematokrit dan Hemoglobin Ikan Sapu-sapu (Pterygoplichthys pardalis) Terpapar Logam Berat Merkuri Klorida - Diah Wulandari Rousdy, Siti Anikha Idzni Junardi (Jurnal Protobiont, 2018)
Mercury chloride (HgCl2) is one of the heavy metals that are harmful to the environment and can accumulate in aquatic organisms, such as Sucker Mouth Catfish, Pterygoplichtys pardalis. The purpose of this study was to analyze the damage of the hematocrite values and hemoglobin of P. pardalis exposed to mercury chloride. This study used a Randomized Block Design method with 54 male fish and six treatment groups, namely Control (0 ppm); P1 (0.01 ppm); P2 (0.02 ppm); P3 (0.04 ppm); P4 (0.08 ppm); P5 (0.16 ppm). Hematological tests showed a significant difference between treatment and control, while the different hemoglobin values with controls only at a concentration of 0.16 ppm. Mercury chloride causes damage to hematological disorders in P. pardalis